2021
DOI: 10.1044/2020_jslhr-20-00142
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in the Online Processing of Spoken Semantic Context and the Effect of Semantic Competition: Evidence From Eye Gaze

Abstract: Purpose The study examined age-related differences in the use of semantic context and in the effect of semantic competition in spoken sentence processing. We used offline (response latency) and online (eye gaze) measures, using the “visual world” eye-tracking paradigm. Method Thirty younger and 30 older adults heard sentences related to one of four images presented on a computer monitor. They were asked to touch the image corresponding to the final word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Two recent studies ( Ayasse and Wingfield, 2020 ; Harel-Arbeli et al, 2021 ) used eye-tracking to compare activation of semantic, rather than phonological, competitors in older and younger adults. Ayasse and Wingfield (2020) compared the time-course of gaze fixations for older and younger adults on sentence-final target items when a semantically plausible competitor was either present or absent as well as for a control condition in which context was not predictive of the sentence final item.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies ( Ayasse and Wingfield, 2020 ; Harel-Arbeli et al, 2021 ) used eye-tracking to compare activation of semantic, rather than phonological, competitors in older and younger adults. Ayasse and Wingfield (2020) compared the time-course of gaze fixations for older and younger adults on sentence-final target items when a semantically plausible competitor was either present or absent as well as for a control condition in which context was not predictive of the sentence final item.…”
Section: Introductionmentioning
confidence: 99%
“…In exploring the temporal dynamics of word recognition, authors could not only gauge the timing of target word recognition, but also determine the level and type of lexical competition that listeners were experiencing. Recent work from our lab also demonstrated that group-differences related to working memory load that were obscured in offline measures (e.g., accuracy) were uncovered when gaging online eye-tracking measures ( Hadar et al, 2016 ; Nitsan et al, 2019 ; Harel-Arbeli et al, 2021 ).…”
Section: Discussionmentioning
confidence: 78%
“…As spoken sentence processing involves many intervening factors, they may inflate the effects of working memory. Among the abilities necessary to understand sentences are sustained attention for the duration of the sentence and maintaining a running memory of the input to relate what is being heard to what has just been heard and to integrate it with what is about to be heard ( Ayasse et al, 2017 ; Harel-Arbeli et al, 2021 ). Further, spoken context processing may be more influenced by linguistic experience and vocabulary than the processing of a single spoken word ( Stine-Morrow et al, 2006 ; Borovsky et al, 2012 ; Ben-David et al, 2015 ; Kavé and Halamish, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was also a convenience sample that may not represent the Israeli adult population. For example, 76% of our responders were women, possibly impacting the results [note, a higher proportion of female participants is not uncommon in this age group; e.g., ( 26 , 49 )]. The study was conducted in Israel with unique cultural aspects ( 51 ).…”
Section: Discussionmentioning
confidence: 99%